Exhibition work at the National Museum of the Republic of Tuva, 1990-2018 - Dyrtyk-ool, Anna O.; Martynov, Anatoly I. (The New Research of Tuva, 2019)
The article examines the leading trends of exhibition work at the National Museum of the Republic of Tuva in the three post-Soviet decades – 1990s,  2000s, and 2010s. Since the start of the 1990s, museums throughout the country, including Tuva, have witnessed a sea change in their role and place in what used to be Soviet society. This drastic turn in the sociocultural situation led to a critical reassessment of history, re-evaluation of the museum funds and a search for new priorities in museum communication. Although new data was critically missing, the opportunity to develop museum projects in a free and creative manner was invaluable.From 1992 to 2000, the museum saw a steady rise in the number of both stationary and mobile exhibitions, the latter being held at various educational institutions, enterprises and other entities in both Kyzyl and the rayons of the region. Stationary exhibitions at these times were largely focused on anniversaries of famous people, primarily contributors to Tuvan culture, and of historical events. Mobile exhibitions also featured a number of topics on material and spiritual culture of Tuvans, or sometimes, Nadya Rusheva’s drawings. The museum was also closely following remarkable events in the life of contemporary Tuva.From 2001 to 2018, the museum has enhanced its work every year. The article provides a review of the most significant exhibitions of these decades, as well as a classification and an overview of each project type. Thematically, both in Tuva and beyond by far the most popular were the exhibitions focused on the life and work of Nadya Rusheva, on material and spiritual culture of Tuvans, and to Tuvan applied and decorative art.For its sources, the article made use of museum documentation, including research plans, exhibition prospects and reports.
Keywords: National Museum of the Republic of Tuva; Tuva; Tuvan culture; shamanism in Tuva; exhibition; exhibition policy; museum; cultural heritage; post-Soviet times